Efficient Multilevel Privacy Preserving Authentication Scheme for Emergency Message Communication in VANE - Santhana Devi, G; Germanus Alex, M (International Journal of Engineering and Technology, 2018)
Vehicular ad hoc networks (VANETs) provide spontaneous traffic related and emergency rescue messages to its users of the route thereby enable them with the trouble-free driving. VANETs send emergency messages in times of exigencies that save people’s lives from disasters. Doing such times it has been a great challenge to ascertain the authentication and privacy of the messages that are broadcasted. Generally when the messages are broadcasted without accommodating privacy the confidential information’s like the vehicle’s id and location are exposed which adversely affect the users. In this paper to ensure privacy to the users we have recommended TA to provide a verification signature to all the vehicles which is mandatory for a vehicle for all its communication purpose. Normally in the existing schemes, the messages are provided with single level or bi level privacy features but, in the proposed scheme the emergency messages are provided with the multilevel privacy features. In the proposed scheme the TA provides a long term  Verification signature which is mandatory to all the vehicles that are registered under VANET and this signature is also necessary in receiving the secondary token and common token from RSU at each interval of time. The authentication of the message is verified with the help of common token and encrypted common token as a RSU Verification signature. Since the emergency messages require secure, timely and factual communication our proposed protocol EMPPA scheme recommend the distribution of multiple verification signatures and tokens at various interval of time, so that the privacy, security and the authentication of messages are ensured to the VANET users.